2021
DOI: 10.1111/asj.13563
|View full text |Cite
|
Sign up to set email alerts
|

Uterine blood flow, fetal heart rate, gestational length, and fetal birth weight variability in response to maternal temperament in the goat

Abstract: This prospective study was designed to investigate the effects of maternal temperament on uterine blood flow, fetal heart rate, gestational length, and fetal birth weight in a goat experimental model. Based on the arena test, behavioral testing related to fear‐eliciting stimulus, goats were divided into nervous (n = 13) and calm (n = 11) groups. After mating, the perfusion of maternal uterine arteries (UTAs) and its related Doppler parameters, blood flow volume (BFV), time‐averaged mean velocity (TAMEANV), acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 106 publications
3
6
0
Order By: Relevance
“…These results indicate higher blood perfusion within the MUA and UMA in the calm goats than in the nervous goats. Our findings matched those of other investigations (Aberdeen et al 2010 ; Vythilingum et al 2010 ; Elmetwally et al 2021 ). It was reported the impact of maternal anxiety on the blood flow within the MUA and UMA in sheep and goats, especially during the second half of gestation (Elmetwally et al 2016b ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These results indicate higher blood perfusion within the MUA and UMA in the calm goats than in the nervous goats. Our findings matched those of other investigations (Aberdeen et al 2010 ; Vythilingum et al 2010 ; Elmetwally et al 2021 ). It was reported the impact of maternal anxiety on the blood flow within the MUA and UMA in sheep and goats, especially during the second half of gestation (Elmetwally et al 2016b ).…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, the nervous goats attained high levels of cortisol either in the sedated or the non-sedated conditions compared to that in the calm one. Similar findings were reported in the pregnant sheep and goats (Elmetwally et al 2016b , 2021 ). Previous studies in cows (Herzog et al 2011 ), small ruminants (Elmetwally et al 2016b , 2021 ), and humans (Fan et al 2018 ) found a close link between increased animal anxiety, cortisol levels, and decreased uterine artery blood flow.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The application of color Doppler ultrasound was proven to be a feasible, safe, accurate method for evaluation of changes in uterine blood ow in cows (3,15), mares (16, 17), buffaloes (18, 19) and small ruminants (20)(21)(22), but there are no reports of studies of vaginal blood perfusion in veterinary reproduction using color Doppler ultrasound.…”
Section: Discussionmentioning
confidence: 99%
“…Ensuring an adequate foetal blood flow is beyond critical for stable and developmental pregnancy (Mandala & Osol, 2012). Uteroplacental hemodynamics is sensitive to many factors, such as nutrition (Eifert et al, 2015), climatic changes (Reynolds et al, 2006) and management (Elmetwally et al, 2021; Hohimer et al, 1984). OS induces uterine blood flow decline, mainly as an effect of low nitric oxide (NO) bioavailability.…”
Section: Introductionmentioning
confidence: 99%